2021
DOI: 10.1371/journal.pone.0249409
|View full text |Cite
|
Sign up to set email alerts
|

Statins for major depressive disorder: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background The burden of depressive disorder is large and new treatment approaches are required. Repurposing widely available drugs such as statins may be a time- and cost-effective solution. Statins have anti-inflammatory and anti-oxidant properties which have been shown to be relevant to the pathophysiology of depression. This study assesses the efficacy, acceptability, tolerability, and safety of statins in major depressive disorder. Methods Our study is an update and extension of a previous meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…They both included 3 RCTs ( 133 135 ) and found a significant improvement in depressive symptoms [SMD = −0.73, 95% CI = −1.04 to −0.42 ( 130 ); SMD = −0.65, 95% CI = −0.96 to −0.33 ( 19 )] associated with statins add-on. A more recent meta-analysis added a further RCT ( 132 ) and confirmed the above results (SMD = −0.48, 95% CI = −0.74 to −0.22], whilst also supporting the acceptability, tolerability, and safety of statins in the treatment of depression ( 71 ).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…They both included 3 RCTs ( 133 135 ) and found a significant improvement in depressive symptoms [SMD = −0.73, 95% CI = −1.04 to −0.42 ( 130 ); SMD = −0.65, 95% CI = −0.96 to −0.33 ( 19 )] associated with statins add-on. A more recent meta-analysis added a further RCT ( 132 ) and confirmed the above results (SMD = −0.48, 95% CI = −0.74 to −0.22], whilst also supporting the acceptability, tolerability, and safety of statins in the treatment of depression ( 71 ).…”
Section: Resultsmentioning
confidence: 65%
“…For example, all the retrieved RCTs (133-135) that employed a lipophilic statin (respectively, lovastatin, atorvastatin, and simvastatin) in depressed patients observed an improvement of depressive symptoms, whereas the only trial that could not replicate this effect used the hydrophilic molecule, rosuvastatin (132). Interestingly, simvastatin, the most lipophilic statin, showed a more pronounced antidepressant effect compared to the less lipophilic atorvastatin in another RCT (131) and fared better than any other statin in a recent exploratory network meta-analysis (71). Likewise, evidence from most observational studies in non-depressed populations reported that simvastatin had the most beneficial effects (87,90), though another study reported a conflicting finding (76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a significant reduction in depressive symptoms in all three groups and no significant differences in the primary or secondary outcomes between groups. In a recent meta-analysis that pooled the results from the aforementioned studies, statins were more efficacious than placebo in addition to antidepressants to reduce depressive symptoms at 8 weeks (N = 255, SMD = −0.48, 95%CI: −0.74 to −0.22) and 12 weeks (N = 134, SMD = −0.47, 95%CI: −0.89 to −0.05); an exploratory network meta-analysis suggested that simvastatin, which is more lipophilic, may be more efficacious than the rosuvastatin, with is less lipophilic [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the most recent meta-analysis of randomized clinical trials on 5 studies and 389 participants, De Giorgi et al reported significant benefits of add-on statins at 8 and 12 weeks of treatment. In comparing statins, simvastatin, the most lipophilic compound, demonstrated a stronger antidepressant capability than atorvastatin [ 62 ]. This was consistent with a previous study on the antidepressant effect of statin in post coronary artery bypass graft with mild-moderate clinical depression, demonstrating a greater efficacy of simvastatin over atorvastatin [ 63 ].…”
Section: Introductionmentioning
confidence: 99%